Pengaruh Gaya Kepemimpinan,Komitmen Dan Komunikasi Organisasi Terhadap Kinerja Pengurus - Moch. Ardiansyah Pramudya; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
AbstractThis study plans to decide and dissect the effect of value, progress, and quality of administration on consumer loyalty of Ayam Geprek Kak Rose in Malang City. This kind of exploration is a reasonable assessment with quantitative methodologies. The strategy used is a different straight relapse. The test procedure uses a recipe from Malhotra with computational consequences of 80 examples. To overcome this problem, this review uses SPSS assistance with legitimacy tests, unshakable quality tests, ordinance tests, various direct relapse tests, multicollinearity tests, heteroscedasticity tests, F tests, and t tests. The results showed that all factors of value, progress, and quality of administration fundamentally affect consumer loyalty, cost basically affects consumer loyalty, progress affects consumer loyalty, and the overall quality of administration affects consumer loyalty. fulfillment. Keywords : Cost, Progress, Administrative Quality, Consumer Loyalty